Intraspecific morphological variation of Scutovertex sculptus Michael (Acari: Oribatida: Scutoverticidae) and description of its juvenile stages - Pfingstl, Tobias; Schäffer, Sylvia; Ebermann, Ernst; Krisper, Günther (Zootaxa, 2008)
This paper provides a detailed redescription of the adult and the first morphological description of all juvenile stages of Scutovertex sculptus. Specimens from four European countries, Austria, Germany, France and Spain were investigated. The species specific characters are the broadened posterior notogastral setae (lp, h 1 –h 3 ), the slightly broadened anterior notogastral seta (dm), the gastronotic cuticle with irregularly distributed foveae and a thick layer of secretion forming blocs with color dispersive qualities on the posterior half of notogastral region. Minor differences in the shape of notogastral setae and in the thickness of the secreted layer on the posterior gastronotic region were found in specimens from different countries. The investigation of the juveniles of S. sculptus showed that the larva and nymphs can be easily distinguished from those of S. minutus; the lateral setae on tibia I are leaf-shaped in S. sculptus and knife-shaped in S. minutus.